2022
DOI: 10.3389/fenvs.2022.971214
|View full text |Cite
|
Sign up to set email alerts
|

Does the carbon trading mechanism affect social and environmental benefits of the retailer-led supply chain: Strategic decisions of emissions reduction and promotion

Abstract: Governments, enterprises, and customers have become more concerned about environmental protection. Following the world’s largest carbon trading market (EU ETS), China has also implemented a market-based carbon trading mechanism (CAT) to reduce CO2. Simultaneously, customers have low-carbon preferences for environmental products. Thus, the enterprises’ strategic decisions and collaboration modes have changed. This article develops the Stackelberg game model to explore the impacts of CAT and customers’ low-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Game order of carbon decision behavior Tong et al (2022) found that carbon trading market prices and customers' low-carbon preferences are key factors influencing the retail price, total carbon emissions, and social welfare. So, the carbon quotas allocation mechanism was set up for the carbon mitigation goal based on the carbon emission rights to form a double market: a primary allocation market of carbon quotas dominated by the government and a secondary trading market of carbon quotas dominated by enterprises.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Game order of carbon decision behavior Tong et al (2022) found that carbon trading market prices and customers' low-carbon preferences are key factors influencing the retail price, total carbon emissions, and social welfare. So, the carbon quotas allocation mechanism was set up for the carbon mitigation goal based on the carbon emission rights to form a double market: a primary allocation market of carbon quotas dominated by the government and a secondary trading market of carbon quotas dominated by enterprises.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…Based on the above background, many scholars have conducted in-depth research on carbon emission reduction outsourcing in the supply chain.Zhou [1] studied the number of orders and profits of a single manufacturer, and the changes of the entire supply chain before and after the implementation of the bilateral monopoly supply chain composed of a single manufacturer and a single retailer.Liang [2] studied emission reduction cost sharing contracts through green innovation under carbon emission constraints, analyzing the optimal cost sharing ratio established by manufacturers and retail prices established by retailers.He [3]studies a service supply chain consisting of service providers responsible for carbon reduction and services and a service integrator of low-carbon advertising for three types of cost-sharing decisions, explore optimal decisions.Ghosh [4]explores supply chain coordination issues arising from the Green Supply Chain Initiative and explores the impact of cost-sharing contracts on key decisions for supply chain participants.Taleizadeh [5] Cost-sharing contracts in a closed-loop supply chain considering carbon reduction, quality improvement efforts and pricing strategies.Wen [6] explores the impact of CAT and customers' low-carbon preferences on carbon emissions reduction and promotion strategies in retailer-led supply chains.Ji [7]analyzes the green financing and emissions reduction decisions of a capital-constrained supply chain composed of a well-funded retailer.Okay [8] believes that Energy Services serves as a professional third-party provider of energy saving and emission reduction projects, and aims to design sustainable energy solutions for businesses.Yuan [9] believes that China is currently facing a severe environmental pollution problem, and contract energy management, as a new market mechanism, can effectively reduce energy consumption.…”
Section: Introductionmentioning
confidence: 99%